2015
DOI: 10.9734/ijtdh/2015/17672
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Literature Review: Podoconiosis in Southwestern Uganda

Abstract: Aims: This report presents one confirmed and two suspected cases of podoconiosis in the Kabale region of southwestern Uganda. Podoconiosis has not previously been described in Uganda outside of the eastern region bordering Kenya. The aim of this case report is to increase awareness of the condition in order to enhance prevention and treatment efforts. Case StudyPresentation of Cases: Podoconiosis is associated with chronic barefoot exposure to red volcanic soil, with greater prevalence in high-altitude, impove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[22][23][24][25][26][27] In Uganda, the disease has been reported on the slopes of Mt Elgon in Kapchorwa in northeastern Uganda (areas rich in volcanic soils), and in the highlands of Kabale and Kisoro districts in southwestern Uganda. 1,22,28,29 However, podoconiosis had never before been recognized in western Uganda (Toro-Ankole region).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27] In Uganda, the disease has been reported on the slopes of Mt Elgon in Kapchorwa in northeastern Uganda (areas rich in volcanic soils), and in the highlands of Kabale and Kisoro districts in southwestern Uganda. 1,22,28,29 However, podoconiosis had never before been recognized in western Uganda (Toro-Ankole region).…”
Section: Discussionmentioning
confidence: 99%
“…A pathological study revealed amorphous and crystalline silicon compounds in macrophages of femoral lymph nodes [ 19 ]. In Uganda, podoconiosis cases were reported from highlands of >1500 m [ 9 , 10 ], while LF distribution was limited in areas lower than 1300 m [ 8 ]. In Ethiopia, however, potential distribution overlap of these two different types of elephantiasis is reported at an altitude of 1225−1698 m [ 20 ], and one report clearly mentions the co-endemicity in western Ethiopia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease is found in the high mountain area, where filariasis does not exist. Three cases of podoconiosis were also reported in the south-western highland in Uganda [ 10 ]. In the course of the study, we encountered several “unusual” elephantiasis cases among people walking barefoot.…”
Section: Introductionmentioning
confidence: 99%